2017
DOI: 10.1038/srep41332
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans stimulates Streptococcus mutans microcolony development via cross-kingdom biofilm-derived metabolites

Abstract: Candida albicans is frequently detected with heavy infection of Streptococcus mutans in plaque-biofilms from children affected with early-childhood caries, a prevalent and costly oral disease. The presence of C. albicans enhances S. mutans growth within biofilms, yet the chemical interactions associated with bacterial accumulation remain unclear. Thus, this study was conducted to investigate how microbial products from this cross-kingdom association modulate S. mutans build-up in biofilms. Our data revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
168
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 62 publications
(109 reference statements)
8
168
0
1
Order By: Relevance
“…Previous studies have reported that C. albicans promotes the growth of S. mutans in the two‐species biofilm, thus enhancing biofilm formation . In contrast, other studies have reported that C. albicans and S. mutans display no synergistic effect, and some reports even document that S. mutans inhibits growth and hyphal formation in C. albicans . Different results may be due to the use of different biofilm conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have reported that C. albicans promotes the growth of S. mutans in the two‐species biofilm, thus enhancing biofilm formation . In contrast, other studies have reported that C. albicans and S. mutans display no synergistic effect, and some reports even document that S. mutans inhibits growth and hyphal formation in C. albicans . Different results may be due to the use of different biofilm conditions.…”
Section: Discussionmentioning
confidence: 96%
“…8 In contrast, other studies have reported that C. albicans and S. mutans display no synergistic effect, and some reports even document that S. mutans inhibits growth and hyphal formation in C. albicans. [31][32][33][34] Different results may be due to the use of different biofilm conditions. In our model we observed that many C. albicans cells were in yeast or pseudohyphal form (Figure 2), which is consistent with previous studies that have shown that in low-pH environments C. albicans is typically found in yeast or pseudohyphal form rather than the hyphal form.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is a key regulator of C. albicans biofilm formation [63], and has also been shown to augment antimicrobial therapy and decrease bacterial biofilm formation [64,65]. These effects are also observed with S. mutans, with high concentrations of the compound inhibiting biofilm formation [66,67]. Yet, interestingly, when at lower concentrations (25-50 μM) that are representative within these dualspecies biofilms, then it can stimulate S. mutans microcolony development and enhance biofilm formation [67].…”
Section: Caries: Slimy Residentsmentioning
confidence: 99%
“…These effects are also observed with S. mutans, with high concentrations of the compound inhibiting biofilm formation [66,67]. Yet, interestingly, when at lower concentrations (25-50 μM) that are representative within these dualspecies biofilms, then it can stimulate S. mutans microcolony development and enhance biofilm formation [67]. It is therefore thought that this is a key maintenance molecule with regard to regulating microbial fitness and biofilm formation in oral plaque [68].…”
Section: Caries: Slimy Residentsmentioning
confidence: 99%
“…This mixed biofilm is embedded in a matrix composed mainly of extracellular α-glucans generated by the activity of the glucosyltransferase B (GtfB) secreted by S. mutans. Mannans present on the outer cell wall of C. albicans mediate GtfB binding leading to the increased production of this matrix and modulation of interaction between bacteria and fungi within biofilm (Ellepola et al, 2017;Hwang et al, 2017;Kim et al, 2017). The cariogenic role of C. albicans is associated with acidogenicity and the fermentation of assimilated dietary sugars, resulting in the production of collagenolytic proteinases.…”
Section: Introductionmentioning
confidence: 99%